Effects of Nerve Growth Factor-β From Bull Seminal Plasma on Steroidogenesis and Angiogenic Markers of the Bovine Pre-ovulatory Follicle Wall Cell Culture - Stewart, Jamie L.; Gao, Liying; Flaws, Jodi A.; Mercadante, Vitor R. G.; Dias, Nicholas W.; Canisso, Igor F.; Lima, Fabio S. (Frontiers in Veterinary Science, 2022)
Nerve growth factor-β (NGF) is critical for ovulation in the mammalian ovary and is luteotrophic when administered systemically to camelids and cattle. This study aimed to assess the direct effects of purified bovine NGF on steroidogenesis and angiogenic markers in the bovine pre-ovulatory follicle. Holstein heifers (n = 2) were synchronized with a standard protocol, and heifers with a preovulatory follicle (≥ 12 mm) had the ovary containing the dominant follicle removed via colpotomy. Pre-ovulatory follicles were dissected into 24 pieces containing theca and granulosa cells that were randomly allocated into culture media supplemented with either purified bovine NGF (100 ng/mL) or untreated (control) for 72 h. The supernatant media was harvested for quantification of progesterone, testosterone, and estradiol concentrations, whereas explants were subjected to mRNA analyses to assess expression of steroidogenic and angiogenic markers. Treatment of follicle wall pieces with NGF upregulated gene expression of steroidogenic enzyme HDS17B (P = 0.04) and increased testosterone production (P < 0.01). However, NGF treatment did not alter production of progesterone (P = 0.81) or estradiol (P = 0.14). Consistently, gene expression of steroidogenic enzymes responsible for producing these hormones (STAR, CYP11A1, HSD3B, CYP17A1, CYP19A1) were unaffected by NGF treatment (P ≥ 0.31). Treatment with NGF downregulated gene expression of the angiogenic enzyme FGF2 (P = 0.02) but did not alter PGES (P = 0.63), VEGFA (P = 0.44), and ESR1 (P = 0.77). Collectively, these results demonstrate that NGF from seminal plasma may interact directly on the theca and granulosa cells of the bovine pre-ovulatory follicle to stimulate testosterone production, which may be secondary to theca cell proliferation. Additionally, decreased FGF2 expression in NGF-treated follicle wall cells suggests hastened onset of follicle wall cellular remodeling that occurs during early luteal development.